2015
DOI: 10.4254/wjh.v7.i16.1982
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: A new therapeutic target for liver fibrosis

Abstract: production and progressive accumulation of ECM can lead to end-stage liver disease. Although significant progress has been achieved in elucidating the mechanisms of fibrogenesis, effective anti-fibrotic strategies are still lacking. Autophagy is an intracellular process of self-digestion of defective organelles to provide material recycling or energy for cell survival. Autophagy has been implicated in the pathophysiology of many human disorders including hepatic fibrosis. However, the exact relationships betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Along with HSCs activation, autophagy flux is up‐regulated. Autophagy may supply energy for activation of HSCs by delivering triglyceride and other components in lipid drops from autophagosomes to lysosomes for degradation 19, 20. Hernández‐Gea et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with HSCs activation, autophagy flux is up‐regulated. Autophagy may supply energy for activation of HSCs by delivering triglyceride and other components in lipid drops from autophagosomes to lysosomes for degradation 19, 20. Hernández‐Gea et al .…”
Section: Discussionmentioning
confidence: 99%
“…Along with HSCs activation, autophagy flux is up-regulated. Autophagy may supply energy for activation of HSCs by delivering triglyceride and other components in lipid drops from autophagosomes to lysosomes for degradation [19,20]. Hern andez-Gea et al found that inhibition of autophagic function in primary mouse HSCs and mice following reduced fibrogenesis and matrix accumulation, which suggested autophagy promoted HSCs activation [21].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-beta (transforming growth factor-beta) signaling systems acting as major growth regulatory pathways crosstalk with mTOR-autophagy genes and apoptosis genes to control cell growth and death1920. In response to the crude extract vs. GCV, six genes related to the TGF-beta were deregulated, including four upregulated genes ( bmpr1aa, bmpr1ba, smad3a , and Rhoab ) and two downregulated genes ( Rhoaa and Rhoac ).…”
Section: Resultsmentioning
confidence: 99%
“…In most of the chronic liver diseases and liver fibrosis, there is significant increase in inflammation and stress followed by vascular remodelling because of extra cellular matrix deposition [2]. Liver injury occurs because of several factors among them the prominent are hepatitis B or hepatitis C virus infections, stress, xenobiotics, alcohol consumption, non-alcoholic steatohepatitis (NASH) [3]. The liver enzymes are unable to degrade scar tissue and the response goes inappropriate and resulting in deposition of more collagen and degradation of elastin in the development of fibrosis [4].…”
Section: Mini Reviewmentioning
confidence: 99%